2017
DOI: 10.11591/.v6i2.6641
|View full text |Cite
|
Sign up to set email alerts
|

Early Weaning Risk Factors for Acute Respiratory Infections

Abstract: <p>Acute respiratory infections (ARIs) still a health problem in the world resulting in high mortality and morbidity. Every year 13 million children under five died, 95% of deaths occur in developing countries and 4.5 million deaths due to respiratory infection. Takes effort and hard work to reduce mortality of children under five are caused by ARIs. ARIs episodes in children under five in the world generally between 3-8 times every year. Breast milk is a natural nutrient that contain IgA (SIgA), IgE, Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study by Rustam et al, in 2019 in Riau Province, Indonesia, reported that infants who did not receive exclusive breastfeeding had a risk of about 1.7 times increasing the incidence of ARI compared to infants who exclusively breastfed after being controlled by smokers at home and immunization variables [ 16 ]. Another study also showed that babies who were weaned early could increase the risk of ARI, where babies who were weaned early had a 2.7 times risk of suffering from ARI compared to babies who were weaned according to their age [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Rustam et al, in 2019 in Riau Province, Indonesia, reported that infants who did not receive exclusive breastfeeding had a risk of about 1.7 times increasing the incidence of ARI compared to infants who exclusively breastfed after being controlled by smokers at home and immunization variables [ 16 ]. Another study also showed that babies who were weaned early could increase the risk of ARI, where babies who were weaned early had a 2.7 times risk of suffering from ARI compared to babies who were weaned according to their age [ 17 ].…”
Section: Introductionmentioning
confidence: 99%